2021
DOI: 10.3390/metabo11020073
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonists for Treatment of Nonalcoholic Fatty Liver Disease and Nonalcoholic Steatohepatitis: An Updated Meta-Analysis of Randomized Controlled Trials

Abstract: To assess the efficacy of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) for treatment of nonalcoholic fatty liver disease (NAFLD) or steatohepatitis (NASH), we performed a systematic review and meta-analysis of randomized controlled trials (RCTs). Three large electronic databases were systematically searched (up to 15 December 2020) to identify placebo-controlled or active-controlled RCTs using different GLP-1 RAs. We included eleven placebo-controlled or active-controlled phase-2 RCTs (involving a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 66 publications
4
129
0
10
Order By: Relevance
“…Also, particular consideration should be given to the potential benefits of antidiabetic drugs such as pioglitazone and sodium-glucose cotransporter 2 (SGLT2) inhibitors, which have been shown to be effective in patients with concurrent T2D and NAFLD [164,165], although larger RCTs are required. Similarly, the use of the glucagon-like peptide 1 (GLP-1) receptor agonists such as liraglutide or semaglutide is very promising as there is evidence that these agents impact liver histology and can also improve cardiovascular outcomes in patients with T2D [166][167][168][169]. Finally, as T2D itself is heterogeneous in its etiology, pathogenesis, and clinical presentation, precision medicine approaches to treat and prevent the disease are being actively investigated but significant barriers to their implementation and research gaps still exist [170].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Also, particular consideration should be given to the potential benefits of antidiabetic drugs such as pioglitazone and sodium-glucose cotransporter 2 (SGLT2) inhibitors, which have been shown to be effective in patients with concurrent T2D and NAFLD [164,165], although larger RCTs are required. Similarly, the use of the glucagon-like peptide 1 (GLP-1) receptor agonists such as liraglutide or semaglutide is very promising as there is evidence that these agents impact liver histology and can also improve cardiovascular outcomes in patients with T2D [166][167][168][169]. Finally, as T2D itself is heterogeneous in its etiology, pathogenesis, and clinical presentation, precision medicine approaches to treat and prevent the disease are being actively investigated but significant barriers to their implementation and research gaps still exist [170].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Liver function parameters also showed signi cant improvements, and considering the decrease in triglycerides, semaglutide was considered to have a bene cial effect on fatty liver. A meta-analysis of the therapeutic effects of GLP-1 RAs, including semaglutide, on nonalcoholic fatty liver disease and nonalcoholic steatohepatitis indicated that GLP-1 RAs reduce hepatic brosis on imaging and decrease ALT and γ-GTP, suggesting the possibility of treating fatty liver with GLP-1 RAs [24].…”
Section: Discussionmentioning
confidence: 99%
“…Liraglutide-induced anorexia is also related with glutamatergic POMC neuron, leading to weight loss [ 169 ]. In patients with NAFLD and NASH, it decreases liver fat contents and improves histological resolution and serum liver enzyme levels without worsening fibrosis [ 170 , 171 ]. It is thought that the effect of liraglutide on weight loss and reduced cardiovascular risk is critical for treatment of NAFLD because the development of NAFLD is based on lipotoxicity and insulin resistance [ 171 , 172 ].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Non-alcoholic mentioning
confidence: 99%
“…In patients with NAFLD and NASH, it decreases liver fat contents and improves histological resolution and serum liver enzyme levels without worsening fibrosis [ 170 , 171 ]. It is thought that the effect of liraglutide on weight loss and reduced cardiovascular risk is critical for treatment of NAFLD because the development of NAFLD is based on lipotoxicity and insulin resistance [ 171 , 172 ]. As studies associated with NAFLD and NASH in rodents showed, liraglutide protects pancreatic β-cells from apoptosis through AKT-mediated survival signaling [ 173 ].…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Non-alcoholic mentioning
confidence: 99%